Musical identities mediate musical development - Hargreaves, David; MacDonald, R.; Miell, D. (Oxford University Press, 2012)
This article has two main aims. The first is to identify those aspects of developmental psychology as a whole that are most useful in trying to explain musical development in particular. The second is to develop the central argument that the study of people's musical identities is an essential part of the explanation of their musical development. The article is organized as follows. The first section summarizes the main theoretical perspectives on musical development since the 1980s. The second section provides representative examples of empirical research from three broad areas—cognitive, social, and affective— and then looks at the cognitive aspects of musical development and learning: This was the predominant emphasis of developmental studies in the 1980s. The third section focuses on the social aspects of musical development, which have come to include the study of personality. The fourth section considers the development of the affective aspects of musical behavior, that is, those concerning emotion.